Fine needle biopsy in differential diagnosis of nodular goiter with autoimmune thyroiditis and differentiated thyroid cancers - M. I. Sheremet; L. P. Sydorchuk; V. O. Shidlovskyi; A. D. Bedenyuk; A. I. Popovych; O. V. Lazaruk (Kazimierz Wielki University, 2017)
We examined 75 women with nodular NGAIT and 12 patients with differentiated thyroid cancer during 2015-2016. We have carried out an immunohistochemical study by means of monoclonal antibodies against Fas, FasL, Bcl-2, P53 and Ki67 antigens using the thyroid gland puncture material.   Thus, compared with known methods of differential diagnosis, the proposed study allows for preoperative stage, with a high probability differentiate NGAIT of DTC, by examining extracts from tissues of the thyroid gland, which, in turn, said the volume of surgery and treatment program.             Abbreviations: NGAIT - nodular goiter combined with autoimmune thyroiditis, TG - thyroid gland, PCE - preoperative cytological examination, DTC- differentiated thyroid cancer.